Prototipe Penerapan PKM Teknologi Tepat Guna dengan Model Metode Kaizen 5S dan Simulasi Evakuasi Bencana Gempa pada SDN Bulakan II Kota Cilegon - Hafidz Hanafiah; Eti Nurhayati Safitri; Farihah Farihah; Nurul Aini; Suhenti Suhenti (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Implementing management using the Kaizen 5S method is one way to find out how an organization is good and neat in managing its activities and operations. The Kaizen 5S method is a method that originates from Japan and has been adopted by countries throughout the world. Meanwhile, an earthquake disaster evacuation simulation is an activity that is made similar to when an earthquake disaster occurs with activities according to the SOP. This research aims to implement the Kaizen method and earthquake disaster evacuation simulation which has been studied in an educational organization at SDN Bulakan II in Cilegon City. The method used is applying the Kaizen method and earthquake disaster evacuation simulation. The results of the implementation conclude that the benefits of these two activities influence management and operational activities.